2008
DOI: 10.1016/j.jhep.2007.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Functional interaction between Wnt3 and Frizzled-7 leads to activation of the Wnt/β-catenin signaling pathway in hepatocellular carcinoma cells

Abstract: Background/Aims-The canonical Wnt signaling is frequently activated in human hepatocellular carcinoma (HCC). We previously demonstrated that up-regulation of Frizzled-7 receptor (FZD7) in HCC was associated with nuclear accumulation of wild-type β-catenin. Here, we investigated Wnt ligand(s) that may activate the Wnt/β-catenin pathway through FZD7 in HCC cells. Results-In hepatitis B virus (HBV)-induced HCC, Wnt3 was upregulated in tumor and peritumoral tissues compared to normal liver and downstream β-catenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
176
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(186 citation statements)
references
References 50 publications
9
176
0
1
Order By: Relevance
“…The noncanonical PKC and JNK pathways have been clearly shown as potentially activated by some FZD family members as FZD7, whereas it remains ambiguous for FZD3 and FZD6 (He et al, 1998;Winklbauer et al, 2001;Kinoshita et al, 2003;Merle et al, 2004;Katoh, 2007;Katoh and Katoh, 2007b). We have previously reported that the FZD7-mediated signalling was able to control the cancerous phenotype of human HCC cell lines through b-catenin protein regulation, and that one of the Wnt ligand candidate activators is WNT3 (Merle et al, 2004(Merle et al, , 2005Kim et al, 2008). Nothing is clear about the functional interaction between FZD7 and WNT4 or WNT5A.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The noncanonical PKC and JNK pathways have been clearly shown as potentially activated by some FZD family members as FZD7, whereas it remains ambiguous for FZD3 and FZD6 (He et al, 1998;Winklbauer et al, 2001;Kinoshita et al, 2003;Merle et al, 2004;Katoh, 2007;Katoh and Katoh, 2007b). We have previously reported that the FZD7-mediated signalling was able to control the cancerous phenotype of human HCC cell lines through b-catenin protein regulation, and that one of the Wnt ligand candidate activators is WNT3 (Merle et al, 2004(Merle et al, , 2005Kim et al, 2008). Nothing is clear about the functional interaction between FZD7 and WNT4 or WNT5A.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we have shown that FZD7 can be activated in vitro by binding of the WNT3 ligand (Kim et al, 2008). In this study, the expression patterns of all 19 WNT, 10 FZD, two LRP, and four sFRP genes have been determined in HCCs and in their matched surrounding precancerous peritumorous areas, by comparison to normal liver (NL) tissues.…”
mentioning
confidence: 97%
“…Furthermore, three other Wnt genes (Wnt3, Wnt4 and Wnt5A), and three FZD genes (FZD3, FZD6 and FZD7) are also upregulated in HCC tissues and preneoplastic peritumoural tissues as compared with normal liver tissues, suggesting that their overexpression may be an early event in hepatocarcinogenesis. However, only the overexpression of FZD7 has been associated with nuclear and/or cytoplasmic accumulation of β-catenin in HCC [70][71][72] .…”
Section: Wnt and Fzdmentioning
confidence: 98%
“…The TCF/LEF family has several spliced forms with unknown functional significance and it is suggested that they may activate preferential genes [86] . In HCC, mutations of TCF-4 are rare with 315 August 10, 2011|Volume 2|Issue 8| WJCO|www.wjgnet.com [70][71][72] phospho-GSK3β High 52 IHC [73] Axin1 Low 67 IHC [76] Dvl High 71 Western blotting [82] Prickle-1 Low 55 PCR [82] HDPR1 Low 58 PCR [83] PIN1 High 53 Western blotting [65] TCF-4 High 91 PCR [87] LEF-1 High 52 IHC [88] CDH17 High 72 IHC [90] CDH17: Cadherin-17; Dvl: Dishevelled; FZD: Frizzled; phospho-GSK3β: Phosphorylated glycogen synthase kinase 3β; HDPR1: Human homologue of Dapper; IHC: Immunohistochemistry; LEF: Lymphoid enhancer factor; PCR: Polymerase chain reaction; PIN1: Peptidyl-prolyl cis/trans isomerase; TCF: T-cell factor.…”
Section: Tcf/lefmentioning
confidence: 99%
“…The Wnt/betacatenin signaling pathway regulates various aspects of development and plays important role in tumor formation in multiple tissues and organs (such as the colon, breast, ovarian, liver, etc.) (Lee et al, 2006;Kim et al, 2008;Yuzugullu et al, 2009). …”
Section: Introductionmentioning
confidence: 99%